2019
DOI: 10.1039/c9ra03683k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of amphiphilic branched silica derivatives associated with oligomeric medium

Abstract: The scheme of ASiP formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In previously work [ 43 ], the cubic structure of the ASiP was established by the NMR spectra. It can be concluded that the ASiP–AGM, obtained at a relatively low content of AGM, is a silica of a cubic structure with an aminopropyl and PEO branches ( Figure 2 ):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously work [ 43 ], the cubic structure of the ASiP was established by the NMR spectra. It can be concluded that the ASiP–AGM, obtained at a relatively low content of AGM, is a silica of a cubic structure with an aminopropyl and PEO branches ( Figure 2 ):…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, silica branched by polyoxyethylene oxide and low-molecular-weight polydimethylsiloxane ( Scheme 1 ) were obtained [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the reaction conditions created, the interaction of PPEG with TDI can be accompanied by the formation of both coplanar polyisocyanate blocks of acetal nature and branched polyisocyanurate structures. In [58], amphiphilic silica derivatives (ASiPs) (Figure 1) associated in an oligomeric medium were synthesized and characterized as modifiers of block copolymers based on macroinitiators and 2,4-toluene diisocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the reaction conditions created, the interaction of PPEG with TDI can be accompanied by the formation of both coplanar polyisocyanate blocks of acetal nature and branched polyisocyanurate structures. In [58], amphiphilic silica derivatives (ASiPs) (Figure 1) associated in an oligomeric medium were synthesized and characterized as modifiers of block copolymers based on macroinitiators and 2,4-toluene diisocyanate. The aim of this work is to develop a route for the synthesis of optically transparent polydimethylsiloxane-ethylene oxide-propylene oxide block copolymers crosslinked with isocyanurates (IMBCs), which have a high sorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic silica derivatives (ASiP) were synthesized in the work [ 47 ] ( Scheme 1 ). It was found that ASiP exhibit co-catalytic activity in the D 4 polyaddition reactions by the anionic mechanism and the ability to be located at the boundary of thermodynamically incompatible phases and, thus, affect the relative position of the components of multi-block copolymers during their formation.…”
Section: Introductionmentioning
confidence: 99%